Single Step Purification of Platelet Factor XIII Using an Immobilized Factor XIII A-Subunit Monoclonal Antibody - Lukacova, Daniela; Reed, Guy L (Thrombosis and Haemostasis, 1993)
To facilitate the analysis of the catalytic subunit of factor XIII we have developed a method for the immunoaffinity purification of this protein from platelets. This method employs a monoclonal antibody that binds to the a-subunit of factor XIII. The anti-factor XIII antibody was immobilized on agarose and then incubated with platelet lysate. Subsequently factor XIII was isolated from the platelet lysate in a single step with a 41% yield as measured by enzyme assay. The purified platelet factor XIII appeared nearly homogeneous when analyzed by polyacrylamide electrophoresis and by immunoblotting with another factor XIII monoclonal antibody.